ANALISIS BUTIR SOAL ULA NGAN AKHIR SEMESTER GASAL MATA PELAJARAN MATEMATIKA KELAS VIII SMP K LASTER 1 KABUPATEN BANYUMAS BERDASARKAN TAKSONOMI BLOOM DUA DIMENSI - Desi Afriani; Kusno Kusno (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2018)
This research aims to describe the composition of cognitive process and knowledge dimension of the item analysis of even final test on mathematic of the fourth grade of SMP cluster 1 Banyumas in academic year 2014/2015, to describe the quality of the even final test based on the theoretical and empirical analysis. Based on the analysis result, the composition of the cognitive process in the item consisted of cognitive process of understanding (35,14%) and applying (64,86%), the knowledge composition consisted of conceptual knowledge (35,14%) and procedural (64,86%). The analysis result of the content validity, multiple choice test, short answer, and essay with the accordingly percentages 96%, 90%, and 80% had fulfilled the criteria of good test. The analysis result of the contruct validity and face validity, multiple choice test, short answer, and essay with the accordingly percentages 92%, 90%, and 80% had fulfilled the criteria of good test. The empirical result analysis showed that the validity level of the item of multiple choice and short answer were dominant in fair category, the essay were dominant in high category, the coefficient reliability of multiple choice, short anwer question, and essay were accordingly 0,62; 0,50; 0,63, the distractor of multiple choice, short answer, and essays were dominant in fair category, the difficulty level of the multiple choice, short answer, and essay were dominant in fair category.